Idiopathic Granulomatous Mastitis: Overcoming this Important Clinical - Emre, A; Akbulut, S; Sertkaya, M; Bitiren, M; Kale, IT; Bulbuloglu, E; Yurttutan, N (2018)
The aim of this study was to determine possible risk factors for recurrence development in patients with idiopathic granulomatous mastitis (IGM). Demographic, clinical, radiologic, and histopathologic characteristics of 34 consecutive patients with IGM were retrospectively reviewed. Also, 32 patients who were informed about recurrence status were divided into non-recurrent (n = 27) and recurrent (n = 5) groups. Both groups were compared for demographic and clinical parameters. This study included 34 female patients with IGM aged between 26 and 70 years (median: 38 years). During the follow-up period, no recurrence occurred in 27 patients whereas recurrence developed in 5 patients. No significant difference was found between the groups with respect to age, lesion size, breast-feeding, number of child, marital status, use of oral contraceptive, familial or personal tuberculosis history, PPD test, smoking, lesion side, lesion location on the breast, and treatment choice. The diagnostic tools of the IGM as follows: tru-cut (n = 18); incisional (n = 6); tru-cut + incisional (n = 5); tru-cut + excisional (n = 2); tru-cut + FNAB (n = 1); FNAB + excisional (n = 1) and FNAB (n = 1). Treatment options were as follow: antibiotics + drainage (n = 10); antibiotics + drainage + corticosteroid (n = 9); wait and watch (n = 6); corticosteroid (n = 3); antibiotics + antituberculous (n = 1); antituberculous (n = 1); antibiotics + breast conserving surgery + chemotherapy (n = 1); modified radical mastectomy+ chemotherapy+ radiotherapy (n=1); and no available (n = 2). This study shows that no demographic and clinical data contributes to the development of recurrence disease. To give a strong message, this study should be supported by other high volume and prospective studies. C1 [Emre, Arif; Sertkaya, Mehmet; Kale, Ilhami Taner; Bulbuloglu, Ertan] Sutcu Imam Univ, Dept Surg, Fac Med, TR-46100 Kahramanmaras, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, TR-44280 Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Liver Transplant Inst, TR-44280 Malatya, Turkey. [Bitiren, Muharrem] Sutcu Imam Univ, Dept Pathol, Fac Med, TR-46100 Kahramanmaras, Turkey. [Yurttutan, Nursel] Sutcu Imam Univ, Fac Med, Dept Radiol, TR-46100 Kahramanmaras, Turkey.